Théophile Gautier and Edgar Poe (Colloquia Comparativa Litterarum, 2025)
The imagination of Théophile Gautier has long time been opposed to that of E. A. Poe, with the argument of a profound difference in sensitivity and imagination between them. No doubt, these differences exist, but they have prevented any serious analysis (there are no studies on the attitude of Gautier to Poe, as evidenced by the large comprehensive bibliography compiled by Paolo Tortonese that we can find on the Internet). However, Gautier was initiated to Poe through Baudelaire, and has demonstrated his knowledge of the works of the American writer by repeated allusions. My intention is to analyse Gautier’s attitude towards Poe's work, especially important when we know how Gautier himself exercised a fundamental influence on the symbolism, on Mallarme and on the aesthetic decadence for which Poe was a master.
Keywords: Gothic fiction; intoxication; magnetic attraction; art for art’s sake; arabesque; decadence